Menyeimbangkan Kebebasan Berserikat dan Ketertiban Umum: Evaluasi Kebijakan Penataan Ormas di Indonesia - Darniyus, Al-Adly (Ministry of Home Affairs, 2026)
The issue of restricting the operational space of mass organizations (ormas) has recently become a significant concern in Indonesia’s democratic discourse. The tension between the need to maintain public order and the obligation to uphold freedom of association has become increasingly evident, particularly amid the rise of coercive administrative policies. This article aims to comprehensively evaluate policies governing mass organizations in Indonesia by examining three purposively selected evaluative dimensions: policy effectiveness, responsiveness to civil society, and their impact on the social order. The study employs a qualitative-descriptive approach through a literature review, analyzing legal documents, institutional reports, and relevant academic literature. The document review focuses on policy dynamics, particularly following the enactment of Law No. 16 of 2017. The analytical method applied is thematic and evaluative document analysis. The findings indicate that policies on mass organizations in Indonesia remain partial and are predominantly characterized by an administrative-repressive approach. In terms of effectiveness, the policies emphasize formal legality rather than the substantive strengthening of organizational capacity. Their responsiveness is also limited due to the lack of public participation in both policy formulation and evaluation processes. From the perspective of social impact, these policies have the potential to constrain civic space and exacerbate social polarization. This study recommends the reformulation of mass organization policies based on the principles of due process, meaningful participation, and the strengthening of constitutional rights protection. Furthermore, insights from international practices—such as the model of militant democracy in Germany and the challenges observed in India—are presented to enrich the discourse on developing more democratic and accountable policy frameworks in Indonesia.